International Monetary Fund Annual Report 1968. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1968)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1968. The report highlights that the performance of the world economy during 1967 was characterized by a mixture of marked progress and serious difficulty. The immediate challenge to stem and reverse the slowdown in economic activity that had begun in 1966 was met effectively. However, the deceleration and subsequent recovery in the trend of activity were accompanied by and contributed to balance-of-payments developments that aggravated longstanding problems.